Scary Storie For Seven Years Old - "Paiba , Helen" (Macmillan Childrens Book: London, 1998)
HORROR & GHOST STORIES, CHILLERS (CHILDREN'S / TEENAGE). Scary Stories for 7 Year Olds is a bright and varied selection of hair raising scary stories by some of the very best writers for children. Perfect for reading alone or aloud - and for dipping into time and time again. With stories from Michael Rosen, Catherine Storr, Jamie Rix, Rose Impey and many more, this book will provide hours of fantastic fun. Ages 7+
Keywords: Horror tales